Updated Tropical Forages Selection Tool for forage prioritization in the global tropics by researchers, academics, farmers and other actors - CGIAR Research Program on Livestock (2021)
The updated Tropical Forages Selection Tool and mobile apps were released in August 2020 and thus available to the end-users. The tool is currently being used on average by >6,500 unique visitors per month from the global Tropics, resulting in >40,000 monthly page views on average.